NETosis in Cancer – Platelet–Neutrophil Crosstalk Promotes Tumor-Associated Pathology - Olsson, Anna-Karin; Cedervall, Jessica (Frontiers in Immunology, 2016)
It has become increasingly clear that circulating immune cells in the body have a major impact on cancer development, progression and outcome. The role of both platelets and neutrophils as independent regulators of various processes in cancer has been known for long, but it has quite recently emerged that the platelet-neutrophil interplay is yet a critical component to take into account during malignant disease. It was reported a few years ago that neutrophils in mice with cancer have increased propensity to form neutrophil extracellular traps (NETs) - web-like structures formed by externalized chromatin and secreted proteases. The initial finding describing this as a cell death associated process has been followed by reports of additional mechanisms for NET formation (NETosis), and it has been shown that similar structures can be formed also without lysis and neutrophil cell death as a consequence. Furthermore, presence of NETs in humans with cancer has been verified in a few recent studies, indicating that tumor-induced NETosis is clinically relevant. Several reports have also described that NETs contribute to cancer-associated pathology, by promoting processes responsible for cancer-related death such as thrombosis, systemic inflammation and relapse of the disease. This review summarizes current knowledge about NETosis in cancer, including the role of platelets as regulators of tumor-induced NETosis. It has been shown that platelets can serve as inducers of NETosis and the platelet-neutrophil interface can therefore be an important issue to consider when designing therapies targeting cancer-associated pathology in the future.